Injection of CO2/N2 gaseous mixtures into gas hydrates to contemporary perform CH4 recovery and CO2 storage - Filipponi Mirko (EDP Sciences, 2021)
Carbon dioxide injection into natural gas hydrate reservoirs represents a promising opportunity to predispose a theoretically carbon neutral energy source. This technique allows to replace methane molecules with an equal number of carbon dioxide molecules and, consequently, to balance in advance emissions associated to methane utilization. While the direct CH4/CO2 replacement has been widely investigated, more data and scientific evidences are required to well define the feasibility of recovering methane by replacing it with CO2-based gaseous mixtures. In this sense, the most promising opportunity consists in flue-gas mixtures. In some cases, the presence of nitrogen was found capable to improve the overall efficiency, due to the direct competition between CH4 and N2 molecules to fill small cages characterizing hydrate structures. Moreover, these mixtures are extremely less-expensive than pure carbon dioxide. In this work, a binary CO2/N2 (50/50 vol%) gaseous mixture was used to recover methane contained into hydrate structures. Experiments were carried out in a small-scale experimental apparatus, designed to simulate a natural gas hydrate reservoir and to intervene on it with replacement techniques. Composition of gaseous mixtures present into hydrates and in the gaseous phase present immediately above, where defined via gas-chromatographic analyses. Finally, results were compared with data currently present in literature, in order to validate their consistency.